Identification and domestication of native ornamental fishes of Begnas Lake, Pokhara, Nepal - Chand, Sapana; Prasad, Archana; Regmi, Ramesh Sharma; Husen, Md Akbal (Nepalese Journal of Zoology, 2022)
Native fishes have great value as an ornamental fish in Nepal as well as in the global fair. Most of the ornamental fish species of Nepal are imported from India and Thailand. The main goal of this experiment is to identify and domesticate indigenous ornamental fishes for commercial production. Begnas area, Pokhara was selected as the study site as it has different small indigenous fish species which might have great potential as ornamental fish. The study was carried out for eight months period from February to September. Native fishes were collected from outlets and irrigation canal of Begnas Lake by using a cast net. Five fish species Puntius conchonius, Puntius sophore, Barilius barna, Danio devario and Danio rerio were identified and found suitable for ornamental purpose. These fish species were domesticated with different feed with maintaining the water quality parameters in an aquarium during the experiment period. Survivability of these fish species was low during the winter season; and at the same time, they could adapt to any kind of food. Danio devario was selected for the breeding purpose; and among all, 33 individuals were selected and placed in different conditions (-in the aquarium with heater and aerator, in the outer tank exposed to direct sunlight, the tank having continuous water flow without sunlight and in the open artificial pool) with 40% CP and bloodworms and maintaining the proper water quality. Out of all the different conditions, the environment that was artificially made pool with enough sunlight was found to be suitable for breeding. Their breeding was also influenced by the environmental condition since they bred one month later than their regular breeding periods in captive conditions.